Digital Degrowth: From Rebound to Regeneration - van der Velden, Maja (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Digitalisation plays a central role in the transition to more sustainable futures. However, it also has negative impacts, such as rebound effects, significantly undermining digitalisation’s efficiency gains. Digital degrowth is a relatively new concept in discourses on sustainable digitalisation. Building forth on the concept of degrowth, first proposed in 1972 and gaining strength in the past 20 years, digital degrowth refers to realigning digital technologies to become regenerative; ecological sound and socially just, while simultaneously contributing to resource efficiency in digitalisation efforts. This exploratory paper reflects on digital degrowth and the rebound effects of digitalisation.